2018
DOI: 10.1186/s12974-018-1341-z
|View full text |Cite
|
Sign up to set email alerts
|

Hashimoto’s thyroiditis induces neuroinflammation and emotional alterations in euthyroid mice

Abstract: BackgroundAlthough studies have reported an increased risk for mood disorders in Hashimoto’s thyroiditis (HT) patients even in the euthyroid state, the mechanisms involved remain unclear. Neuroinflammation may play a key role in the etiology of mood disorders in humans and behavioral disturbances in rodents. Therefore, this study established a euthyroid HT model in mice and investigated whether HT itself was capable of triggering neuroinflammation accompanied by emotional alterations.MethodsExperimental HT was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 74 publications
4
34
0
Order By: Relevance
“…In Hashimoto's thyroiditis mice, IDO1 and SERT are upregulated, accompanied by reduced frontal cortex 5-HT levels. This indicates that alterations in 5-HT signaling in the frontal cortex may be associated with mood control in Hashimoto's thyroiditis patients (107). In Balb/c mice of experimental antiphospholipid syndrome, nervous or mental abnormity such as cognitive deficits and hyperactivity are confirmed to be linked with the up-regulation of 5-HT 1A receptors in the hippocampal and cortical regions (108).…”
Section: Othersmentioning
confidence: 91%
“…In Hashimoto's thyroiditis mice, IDO1 and SERT are upregulated, accompanied by reduced frontal cortex 5-HT levels. This indicates that alterations in 5-HT signaling in the frontal cortex may be associated with mood control in Hashimoto's thyroiditis patients (107). In Balb/c mice of experimental antiphospholipid syndrome, nervous or mental abnormity such as cognitive deficits and hyperactivity are confirmed to be linked with the up-regulation of 5-HT 1A receptors in the hippocampal and cortical regions (108).…”
Section: Othersmentioning
confidence: 91%
“…Clinical studies have suggested that HT is associated with the occurrence of papillary thyroid carcinoma (3). One study suggested that in normal thyroid function, HT can also cause neuroinflammation, leading to emotional alterations (4). At present, the incidence of HT is also increasing; most patients do not show symptoms, often found in the physical examination.…”
Section: Introductionmentioning
confidence: 99%
“…Tg-induced thyroiditis in susceptible mice is a classic model of HT to explore the pathogenesis and therapeutics of HT [40]. A Tg-induced euthyroid HT mouse model previously established in our laboratory was used for the study [41]. Thus, to examine the isolated effect of euthyroid HT on embryo implantation, this study utilized female NOD mice immunized with porcine Tg, resulting in pronounced diffuse enlargement of the thyroid gland, the production of intrathyroidal mononuclear cell infiltration and rising serum Tg-Ab and TPO-Ab antibodies without accompanying FT3, FT4 and TSH abnormalities in serum and the local endometrium, which defines euthyroid HT in humans.…”
Section: Discussionmentioning
confidence: 99%